Dehydration induced transcriptomic responses in two Tibetan hulless barley (Hordeum vulgare var. nudum) accessions distinguished by drought tolerance - Liang, Junjun; Chen, Xin; Deng, Guangbing; Pan, Zhifen; Zhang, Haili; Li, Qiao; Yang, Kaijun; Long, Hai; Yu, Maoqun (BMC genomics, 2017)
The harsh environment on the Qinghai-Tibetan Plateau gives Tibetan hulless barley (Hordeum vulgare var. nudum) great ability to resist adversities such as drought, salinity, and low temperature, and makes it a good subject for the analysis of drought tolerance mechanism. To elucidate the specific gene networks and pathways that contribute to its drought tolerance, and for identifying new candidate genes for breeding purposes, we performed a transcriptomic analysis using two accessions of Tibetan hulless barley, namely Z772 (drought-tolerant) and Z013 (drought-sensitive). There were more up-regulated genes of Z772 than Z013 under both mild (5439-VS-2604) and severe (7203-VS-3359) dehydration treatments. Under mild dehydration stress, the pathways exclusively enriched in drought-tolerance genotype Z772 included Protein processing in endoplasmic reticulum, tricarboxylic acid (TCA) cycle, Wax biosynthesis, and Spliceosome. Under severe dehydration stress, the pathways that were mainly enriched in Z772 included Carbon fixation in photosynthetic organisms, Pyruvate metabolism, Porphyrin and chlorophyll metabolism. The main differentially expressed genes (DEGs) in response to dehydration stress and genes whose expression was different between tolerant and sensitive genotypes were presented in this study, respectively. The candidate genes for drought tolerance were selected based on their expression patterns. The RNA-Seq data obtained in this study provided an initial overview on global gene expression patterns and networks that related to dehydration shock in Tibetan hulless barley. Furthermore, these data provided pathways and a targeted set of candidate genes that might be essential for deep analyzing the molecular mechanisms of plant tolerance to drought stress.